Multi‐Functional Edible Film with Excellent UV Barrier Performance and Accurate Instant Ion Printing Capability. (11th May 2020) - Wang, Zi; Tang, Lirong; Lin, Fengcai; Shen, Yanping; Chen, Yandan; Chen, Xuerong; Huang, Biao; Lu, Beili
Abstract: Using natural biomass resources to synthesize degradable membrane materials, which may replace traditional plastics, is one of the strategies that can reduce pollution. Herein, a mechanochemical method for preparation of degradable biofilm tannic acid‐modified microfibrillated cellulose (TA@MFC)‐G is proposed. The method involves modification of a microfibrillated cellulose (MFC) with plant polyphenol (tannic acid), followed by complexation with gelatin in an aqueous solution. Compared with pure gelatin film, MFC film has higher intrinsic crystallinity and thermal stability. Due to the synergistic effect of tannin and MFC, the mechanical strength and flexibility of the films are improved; its tensile strength is higher than 75 MPa and its elongation at break is as high as 13%. The films also have high UV blocking ability. Finally, the films are printed using Fe 3+ ions or conventional ink, from which it is observed that the pattern printed using Fe 3+ ions has higher solvent resistance and water repellency compared to that printed using conventional ink. This biodegradable film may have promising applications as food packaging materials or in other industries. Abstract : An all‐natural sustainable packaging membrane based on hydrogen bond is successfully constructed via a ball milling technique. The composite membrane display improves mechanical performance and UV blocking efficiency. A novel ion printing method guarantees accurate and instant pattern display based on the metal ion complexing effect.